2018
DOI: 10.21873/invivo.11463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Weight and Body Composition After Gastrectomy Between Elderly and Non-elderly Patients With Gastric Cancer

Abstract: Background: Body weight, especially lean body mass, significantly decreases after gastrectomy for gastric cancer due to surgical invasion, reduced food intake, and reduced mobility, which can reduce the quality of life and induce associated toxicity or reduce compliance with adjuvant chemotherapy. Such risks can be particularly high in elderly patients with gastric cancer. However, whether or not changes in the weight and body composition differ between elderly and non-elderly patients remains unclear. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…However, there was no significant effect of nutrition knowledge, attitude, and practice on postoperative body weight loss. Consistent with some scholars' findings (Aoyama et al, 2019;Davis et al, 2016), our study verified that age was not a risk factor for postoperative body weight loss during 3 months after gastrectomy. Recently, Aoyama et al found that postoperative lean body mass decreased significantly in elderly compared with non-elderly rather than body weight (Aoyama et al, 2019).…”
Section: Factors Contributed To Body Weight Change After Gastrectomysupporting
confidence: 92%
See 2 more Smart Citations
“…However, there was no significant effect of nutrition knowledge, attitude, and practice on postoperative body weight loss. Consistent with some scholars' findings (Aoyama et al, 2019;Davis et al, 2016), our study verified that age was not a risk factor for postoperative body weight loss during 3 months after gastrectomy. Recently, Aoyama et al found that postoperative lean body mass decreased significantly in elderly compared with non-elderly rather than body weight (Aoyama et al, 2019).…”
Section: Factors Contributed To Body Weight Change After Gastrectomysupporting
confidence: 92%
“…The results of GEE showed significant main effect of preoperative BMI categories on body weight change after gastrectomy. Same as the findings in previous study (Aoyama et al, 2019;Shuai et al, 2019;(Tang et al, 2018)), we found that the percentage of body weight loss showed a downward trend as a whole within 3 months after gastrectomy, and the percentage of body weight loss within the first month postoperative period was significantly more than that in the third month postoperative. Similar to the findings in the study of Tanabe et al who found that higher preoperative BMI, was independent predictors of greater body weight loss at the first one year mark after gastrectomy (Tanabe et al, 2017).…”
Section: Factors Contributed To Body Weight Change After Gastrectomysupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies have shown that physical exercise has a great impact on human body mechanisms and functions. Excessive high-load exercise training can damage human body functions, but proper physical exercise can effectively improve the patient's body mechanisms [22,23]. rough exercise, patients with dyslipidemia can change their body shape and composition, reduce fat and sugar in the body, achieve fitness goals, and at the same time help their recovery.…”
Section: Exercise Methods For Patients With Dyslipidemiamentioning
confidence: 99%
“…Aoyama et al revealed that mean body weight loss at 1 month reached 3.4 kg (5.90% of body weight) compared with preoperative mean body weight in Japanese subjects (Aoyama et al 2016). The team of Aoyama et al also found that mean body weight loss value at 1 month and 3 months after surgery were 6.5% and 9.0% respectively in the elderly, while 6.0% and 8.1% respectively in the non-elderly from the preoperative value, but the difference of weight loss over time between elderly and non-elderly was not significant (Aoyama et al 2019). In China, researchers found that mean body weight loss up to 5.8-8.8 kg at 1 month (Shuai et al 2019), and 6.33 kg at 3 months (Tang et al 2018) after gastrectomy compared with preoperative body weight.…”
Section: Body Weight Change After Gastrectomymentioning
confidence: 98%